2021
DOI: 10.1037/spy0000260
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of stability and change of achievement goals for self-regulated motor learning processes and outcomes.

Abstract: Self-regulated motor learning is a frequent and important achievement activity in sport and exercise contexts. Therein, individual learners' achievement goals can be considered relevant for motor learning processes and outcomes. To better understand their role, we first examined the temporal stability of achievement goals during self-regulated motor learning. Next, we tested the relevance of the goals and their temporal variability for the learning process (learning time, effort, and motivational problems) and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Therefore, future research should consider a broad array of course features and how these might matter for the effects of performance goals. Specifically, it might be the case that performance goals matter less for achievement behaviors within settings in which social comparisons are restricted or fellow students are not directly present [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, future research should consider a broad array of course features and how these might matter for the effects of performance goals. Specifically, it might be the case that performance goals matter less for achievement behaviors within settings in which social comparisons are restricted or fellow students are not directly present [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) has defined mental health, referring to a condition of optimal psychological well-being, characterized by an individual’s awareness and utilization of their abilities, effective management of everyday pressures, productive work performance, and active participation in their community. The reason for such interest lies in the fact that empirical research has consistently shown that emotional and cognitive factors play a crucial role in influencing athletes’ performance and career trajectory [ 1 , 2 , 3 , 4 , 5 ]. Indeed, through the integration of physical, cognitive, and emotional aspects, athletes can attain the intended degree of psychological equilibrium and optimize their performance [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coping methods are therefore crucial to the way in which athletes handle these difficulties and uphold their overall well-being and performance [ 57 ]. Coping strategies encompass the intellectual and behavioral actions that individuals employ to effectively handle or adjust to challenging circumstances, pressures, or requirements [ 2 ]. In the field of sport psychology, coping refers to the various psychological, emotional, and behavioral reactions that players employ to manage the pressures associated with their athletic pursuits [ 2 , 58 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An established motivational framework that has been effectively used to describe these qualitative motivational differences in athletes and how they are associated with experiences and behaviors is Achievement Goal Theory (e.g., Fernández-Rio, Cecchini Estrada, Mendez-Gimenez, Fernández-Garcia, & Saavedra, 2014;Isoard-Gautheur, Guillet-Descas, & Duda, 2013;Kavussanu, 2006;Mascret, Elliot, & Cury, 2015;Van Yperen, Blaga, & Postmes, 2014). According to the achievement goal approach, the different goals that individuals pursue guide their interpretations, behaviors, and reactions (including patterns of coping and emotion) in achievement situations (Daumiller et al, 2021;Kaplan & Maehr, 1999;Tuominen-Soini, Salmela-Aro, & Niemivirta, 2008). Thus, elite athletes should interpret and handle stressors differently depending on the personal goals they pursue, as their goals may directly matter for burnout and psychosomatic stress, and indirectly through their use of adaptive coping strategies (see also Ntoumanis, Biddle, & Haddock).…”
mentioning
confidence: 99%